Ethnic Knowledge of Magar on Treatment Practice in Morang District - Bhurtel, Khem Kumar; Magar, Keshar Jung; Ghimire, Sita Ram; Poudel, Ganga Ram (Teacher Half-Yearly Journal, 2025)
The Magar community in Nepal has a rich heritage of health and healing practices, including Jharphuk, shamans who treat illnesses using a holistic approach. Their practices involve spiritual, psychological, and physical dimensions, emphasizing communal support and preserving their cultural heritage. Health practices change over human development, influenced by knowledge and experiences. Nepal's diverse healthcare practices, including indigenous healing practices, offer alternative medicine. This paper explores the health status of Magar, an indigenous Nepali nationality, and their traditional healing practices in Morang district, focusing on their socio-cultural conditions and treatment practices. The ethnographic study investigated socio-cultural presentation, historical information, and disease treatment patterns using exploratory and analytical designs, utilizing descriptive data from selected respondents and key informants. It examines the Magar population in Morang District and Kerabari Rural Municipality, focusing on ward 7 and Jharphuk highlighting inadequate health facilities and skilled manpower. The research used primary and secondary sources, including literature reviews, interviews, field visits, and interviews with traditional healers to gather information on health practices, treatment systems, and ethnic knowledge. It also explores the traditional healing practices and beliefs of the Magar community in Nepal, emphasizing their importance in their healthcare system. It suggests enhancing healthcare by professionalizing healers, promoting health education, and integrating indigenous treatments with modern medicine.